Pelatihan Komputer Akuntansi Dengan Menggunakan Accurate Offline Di SMK PGRI 1 Jakarta - Wijayanti, Dian (Lembaga Teewan Journal Solutions, 2026)
This Community Service Program aimed to enhance the digital accounting competencies of students and teachers at SMK PGRI 1 Jakarta through training on the Accurate Offline application as a support tool for accounting computer learning and preparation for the Competency Certification Examination (USK). The novelty of the program lies in the implementation of an integrated competency-based training model that combines teachers and students within a single learning process, supported by competency test case-based practice modules, hands-on training, and intensive mentoring. The program methodology consisted of needs assessment, module development, pre-testing, material delivery, demonstrations, direct practice sessions, case simulations, mentoring, post-testing, and participant satisfaction evaluation. Evaluation instruments included a knowledge test and a questionnaire, both validated through expert judgment involving two accounting lecturers and one accounting software practitioner. Data were analyzed using descriptive quantitative methods by comparing pre-test and post-test percentage scores. The participants consisted of 26 students and 4 accounting teachers. The results indicated improvements across all competency indicators. On average, the proportion of participants who demonstrated understanding of the material increased from 25.8% to 70.2%, while the proportion categorized as not understanding decreased to nearly 0%. The highest improvement was observed in the competency of preparing opening trial balances, with 81% of participants achieving the “understanding” category in the post-test. These findings demonstrate that the implemented training model was effective in improving digital accounting competencies, strengthening participants’ readiness for competency certification, and supporting the alignment of graduate competencies with industry requirements.